Efektivitas Pemberian Cookies Tepung Kelor dengan Penambahan Tepung Ubi Banggai dan Tepung Kedelai sebagai Alternatif Makanan Tambahan dalam Meningkatkan BB pada Balita Wasting - Nurasmi Nurasmi; Irnawati Irnawati (Jurnal Keperawatan Muhammadiyah, 2023)
Background : The health status of infants and toddlers is a determinant of the quality of human resources. In toddlerhood, growth and development occur very quickly, so a high intake of nutrients is needed. Provision of nutrition that is not optimal for toddlers will cause nutritional problems, one of which can occur is wasting (undernutrition). Indonesia is a developing country that has malnutrition problems including wasting. A public health problem is considered serious if the prevalence of wasting is between 10.0-14.0% and is considered critical if it is ≥15.0%3.Objective: The aim of this research is to produce PMT cookies for toddlers with the addition of moringa flour, Banggai’s sweet potato flour and soybean flour and to analyze the effectiveness of giving cookies made from moringa flour with the addition of Banggai’s sweet potato flour and soybean flour on weight gain in toddlers wasting.Methods: The study used a quasi-experimental one group pre and post-test. Respondents in this study were wasting toddlers in Donggala district. The research was carried out from July to October 2022.Result: The results showed that the selected cookie formulation was based on organoleptic tests on 30 panelists with 70% wheat flour, 10% moringa flour, 10% Banggai’s sweet potato flour and 10% soybean flour. With a moisture content of 3.41%, ash content of 0.364%, protein 37.4% and fat 4.86%. The stages of giving interventions showed that the result value was p = 0.000 (<0.5) this means that giving cookies had an effect on increasing the respondent's body weight. There was an increase in weight in wasting toddlers.Conclusions: The conclusion is that cookies contain nutrients that can increase weight in toddler wasting.